Aplikasi Pencarian Pondok Pesantren Terdekat Menggunakan Algoritma Haversine di Daerah Istimewa Yogyakarta - Adi Yusuf Ar Rasyid; Arifin A Abd Karim (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management, 2022)
After the enactment of Law Number 18 of 2019 concerning Islamic Boarding Schools, now Islamic boarding schools have officially become one of the educational institutions that are recognized for their diplomas, as are other levels of education in general. This makes it a special attraction for people who want their children to get the best education based on religion at Islamic boarding schools, especially in the Special Region of Yogyakarta which is one of the cities of education in Indonesia. Based on the data directory of Islamic boarding schools in 2021/2022 owned by the Indonesian Ministry of Religion, there are 319 Islamic boarding schools in the Yogyakarta Region. With this number of Islamic boarding schools, there are still many Islamic boarding schools whose information is not known which makes it difficult for people to get information from these pesantren. Therefore, the author wants to build an android-based application system that can make it easier for people when they want to find information and the location of Islamic boarding schools with the closest routes around them. The author uses the Kotlin programming language to build Android applications, the method used in finding the nearest route and location uses the Haversine Algorithm formula, the Mapbox API is used to determine the route or line traffic, and the testing method uses Black-Box testing. This application will be useful as a medium that can provide information about Islamic boarding schools with the closest route in the special area of Yogyakarta so that the existence of Islamic boarding schools will be known more widely.